2010
DOI: 10.1073/pnas.1012257107
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of preexisting hyperglycemia in diabetic mice by acute deletion of the Men1 gene

Abstract: A hallmark of diabetes is an absolute or relative reduction in the number of functional β cells. Therapies that could increase the number of endogenous β cells under diabetic conditions would be desirable. Prevalent gene targeting mouse models for assessing β-cell proliferation and diabetes pathogenesis only address whether deletion of a gene prevents the development of diabetes. Models testing whether acute excision of a single gene can ameliorate or reverse preexisting hyperglycemia in established diabetes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 34 publications
4
62
0
Order By: Relevance
“…As menin was previously reported to be downregulated during adaptive b-cell proliferation (Karnik et al, 2007), we also examined menin expression and its potential correlation with MafB reexpression in pregnant (Supplementary Figure S4) or high-fat-fed mice (data not shown). No decrease in menin expression was evident in both conditions, consistent with a recent report where menin expression levels in islets were found unchanged in mice fed with a high-fat diet (Yang et al, 2010), thus no correlation could be found between ectopic MafB expression and menin expression levels.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…As menin was previously reported to be downregulated during adaptive b-cell proliferation (Karnik et al, 2007), we also examined menin expression and its potential correlation with MafB reexpression in pregnant (Supplementary Figure S4) or high-fat-fed mice (data not shown). No decrease in menin expression was evident in both conditions, consistent with a recent report where menin expression levels in islets were found unchanged in mice fed with a high-fat diet (Yang et al, 2010), thus no correlation could be found between ectopic MafB expression and menin expression levels.…”
supporting
confidence: 91%
“…Furthermore, as shown in Figure 4a, we observed that MAFBoverexpressing bTC3-cells displayed the upregulated expression of both Cyclin D2, a previously identified MafB target gene in myeloma cells (van Stralen et al, 2009), and Cyclin B1 (Figure 4a). Factors in both Cyclin D and Cyclin B families were previously reported to be upregulated in mouse Men1 insulinomas (Fontaniere et al, 2006) and in mouse b-cells, with acute Men1-ablation (Yang et al, 2010). To confirm the above results, MafB was knocked-down by siRNA transfec- þ / þ -RipCre þ and three Men1 F/F -RipCre À mice, respectively) by real-time RT-PCR was carried out as previously described (Fontaniere et al, 2006).…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…They were then crossed with Ubc9 promoter driven Cre-ER mice (C57B6 background) as previously described (19). Men1 f/f and Men1 f/f ;Cre-ER mice were as described previously (20). Animal genotyping was done by PCR according to published methods using DNA extracted from tails.…”
Section: Methodsmentioning
confidence: 99%
“…We next speculated that an autocrine factor produced by tumor cells promotes the loss of insulin expression. We explored transcriptomic analyses of Men1-KO ␤-cell and insulinoma models (29,30), looking for candidates known to inhibit insulin expression. Given the importance of TGF-␤ signaling in insulin synthesis and maintenance of ␤-cell maturity (24, 31), we paid particular attention to related ligands.…”
Section: Resultsmentioning
confidence: 99%